2023
DOI: 10.1038/s41392-023-01430-7
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways in vascular function and hypertension: molecular mechanisms and therapeutic interventions

Abstract: Hypertension is a global public health issue and the leading cause of premature death in humans. Despite more than a century of research, hypertension remains difficult to cure due to its complex mechanisms involving multiple interactive factors and our limited understanding of it. Hypertension is a condition that is named after its clinical features. Vascular function is a factor that affects blood pressure directly, and it is a main strategy for clinically controlling BP to regulate constriction/relaxation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(21 citation statements)
references
References 668 publications
(708 reference statements)
0
21
0
Order By: Relevance
“…Studies have shown that RhoA/MAPK can promote the proliferation, migration and differentiation of VSMCs during hypertension [ 11 , 17 , 18 ]. Therefore, we examined the changes in the expression of this pathway in vitro and in vivo .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that RhoA/MAPK can promote the proliferation, migration and differentiation of VSMCs during hypertension [ 11 , 17 , 18 ]. Therefore, we examined the changes in the expression of this pathway in vitro and in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that SPMs, including RvD1, can inhibit the constriction of the rat thoracic aorta and human pulmonary artery induced by the thromboxane mimetic U46619 [ 44 ]. The contractility of VSMCs is related to cytosolic Ca 2+ concentrations and the Ca 2+ sensitivity of myofilaments, and it has been well documented that the RhoA-related signaling pathway is involved in this process [ 17 , 45 ]. Therefore, RvD1 improves hypertension not only by improving the cellular function of VSMCs but also by correcting the abnormal contractility of VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular function is widely regarded as the direct cause of high blood pressure. The primary actors in vascular function are the endothelial and smooth muscle cells 75 . Numerous studies have investigated endothelial dysfunction triggered by LPS.…”
Section: Molecular Mechanisms Between Gut Microbiome and Osa Cvds And...mentioning
confidence: 99%
“…[55] Hypertension (HP) Blood pressure is mainly controlled by blood vessels, and inflammation has been implicated in various pathological processes leading to HP. [56] In animal models of HP, increased blood pressure is linked to low Foxp3 expression, reduced numbers of Tregs, and impaired function of Tregs. [57] Angiotensin II (Ang II) upregulates the expression of monocyte chemoattractant protein-1 in the vascular system, which is well-known for its role in promoting the infiltration of various immune cells associated with HP.…”
Section: Asmentioning
confidence: 99%